Reducing Fatigue in Chronic Kidney Disease Patients Through Benson Relaxation Therapy: Evidence from a Pretest-Posttest Study - Noah Safna Sayla; Lily Wahyuni Romadhon; Citra Setyo Dwi Andhini (STIKES Columbia Asia Medan, 2026)
Chronic Kidney Disease (CKD) is a progressive and irreversible disorder requiring hemodialysis as renal replacement therapy. Fatigue is a frequent symptom among hemodialysis patients and negatively affects quality of life and daily activities. This case study aimed to determine the effect of the Benson relaxation technique on fatigue in a CKD patient undergoing hemodialysis at RSUD Gunung Jati, Cirebon. The method used was a single-subject descriptive case study with nursing intervention applied in three sessions during pre, intra, and post hemodialysis periods. Data were obtained through assessment, observation, and fatigue evaluation. The intervention consisted of deep breathing combined with repetition of calming spiritual or meaningful words according to patient belief. Results showed a decrease in fatigue, indicated by reduced weakness, increased relaxation, improved comfort, and better emotional stability. The patient also reported increased energy after the intervention period. This study suggests that the Benson relaxation technique can be an effective non-pharmacological nursing intervention to reduce fatigue in hemodialysis patients and may be applied as a complementary approach in nursing care.